Strategies and Reforms in Islamic Religious Education Facing Globalization Challenges - Aaliyah Safira Hidayat; Marsanda Adelia Putri; Dwi Septi Ummi Kulsum; Ro’ifah Ro'ifah (Ngaji: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (PAI) encounters diverse complex barriers during the globalization period characterized by ethical regression, sociocultural transformation, and technological acceleration, requiring comprehensive approaches and renewals to remain meaningful and productive. This research attempts to identify obstacles experienced by PAI during globalization, formulate comprehensive learning approaches, and examine the necessary systematic renewal framework. This research employs library review methods with descriptive-analytical approaches through information gathering from various scientific literature sources, academic journals, books, and related articles. Information analysis is conducted qualitatively using content analysis techniques to identify patterns and main ideas related to obstacles, approaches, and PAI renewal. Research findings show that PAI obstacles possess multidimensional characteristics, covering external obstacles (foreign cultural penetration, identity confusion, technological evolution) and internal obstacles (knowledge dichotomy, shortage of teaching hours, lack of educator professionalism). PAI approaches include global generation preparation, paradigm development based on the Qur'an and Sunnah, meaningful curriculum development, technology utilization, and continuous evaluation implementation. PAI renewal requires transformation in philosophical-curricular, structural-institutional, and sociocultural dimensions. Systematic PAI transformation becomes the foundation for producing globally superior Muslim generations while maintaining authentic Islamic identity. Subsequent research needs to explore empirical implementation of PAI approaches and renewals at various learning levels.